School (socie)ties: individual and school level differences in the association between ethnic/racial victimization and academic functioning - da Cunha, Josafá M.; Santo, Jonathan B. (Frontiers in Education, 2023)
Introduction The current study aimed to expand on the existing literature by examining the effect of race-based victimization on academic functioning in a nation-wide sample of Brazilian youth. Methods The ENEM 2009 dataset contained academic functioning scores of 795,924 Brazilian students from 25,488 schools. Results Above and beyond the effect of general victimization, ethnic/racial victimization was significantly negatively related to academic functioning with differences across ethnic/racial groups in the effects. More interesting is that diversity climate at the school level buffered the association between ethnic/racial victimization and academic functioning. The effects were further qualified by school level ethnic/racial diversity and victimization. Discussion The current findings illustrate the pernicious effects of ethnic/racial victimization even after controlling for other forms of victimization. Moreover, differences in these associations across schools were accounted for using a combination of school level racial diversity and victimization with school level diversity climate emerging as a buffer of the effects of ethnic/racial victimization.